Improved Thermoelectric Properties in Melt-Spun SnTe - Ibrahim, Dorra (ACS Omega, 2017)
[Image: see text] SnTe has been the focus of numerous experimental and theoretical studies over the last years owing to its high thermoelectric performances near 800 K when appropriately doped. Here, we demonstrate that melt-spinning, an ultrafast-quenching synthesis technique, followed by spark plasma sintering results in enhanced ZT values in polycrystalline SnTe. To illustrate the impact of this technique, the results are contrasted with those obtained on two polycrystalline samples prepared by direct quenching of molten SnTe and without quenching. SnTe melt-spun ribbons are characterized by a peculiar columnar microstructure that contributes to lower the lattice thermal conductivity below 700 K in pressed samples. More importantly, this technique results in a significant decrease in the hole concentration, giving rise to enhanced thermopower values above 500 K. The variation in the hole concentration is likely due to a slight loss of elemental Te during the melt-spinning process. Thanks to the decreased hole concentration, the thermoelectric performances are significantly enhanced with a peak ZT value of 0.6 at 800 K, which represents a 40% increase over the values measured for samples prepared with and without quenching. These findings indicate that melt-spinning provides a novel strategy to improve the thermoelectric properties of SnTe that could be worthwhile extending to substituted compounds.